(untitled) (Global Journal of Medical Research, 2018)
Leptospirosis is a disease caused by leptospira a spirochete which involves multiple organs. Towering high transaminase levels in the severe form of the disease are unheard of till date. Thus we are going to present the story of a 32-yearmale, with an initial SGPT level of 3520 U/lit who came up with the diagnosis of leptospirosis and recovered due to timely initiation of antimicrobials and hemodialysis.